Single-nuclei sequencing of skeletal muscle reveals subsynaptic-specific transcripts involved in neuromuscular junction maintenance - Alexander S. Ham; Shuo Lin; Alice Tse; Marco Thürkauf; Timothy J. McGowan; Lena Jörin; Filippo Oliveri; Markus A. Rüegg (Nature Communications)
Abstract The neuromuscular junction (NMJ) is the synapse formed between motor neurons and skeletal muscle fibers. Its stability relies on the continued expression of genes in a subset of myonuclei, called NMJ myonuclei. Here, we use single-nuclei RNA-sequencing (snRNA-seq) to identify numerous NMJ-specific transcripts. To elucidate how the NMJ transcriptome is regulated, we also performed snRNA-seq on sciatic nerve transected, botulinum toxin injected, and Musk knockout muscles. The data show that NMJ gene expression is not only driven by agrin-Lrp4/MuSK signaling but is also affected by electrical activity and trophic factors other than agrin. By selecting the three NMJ genes Etv4, Lrtm1, and Pdzrn4, we further characterize novel contributors to NMJ stability and function. AAV-mediated overexpression shows that Etv4 is sufficient to upregulate the expression of −50% of the NMJ genes in non-synaptic myonuclei, while AAV-CRISPR/Cas9-mediated muscle-specific knockout of Pdzrn4 induces NMJ fragmentation. Further investigation of Pdzrn4 revealed that it localizes to the Golgi apparatus and interacts with MuSK protein. Collectively, our data provide a rich resource of NMJ transcripts, highlight the importance of ETS transcription factors at the NMJ, and suggest a novel pathway for NMJ post-translational modifications.